Integrated management of atypical parkinsonism: a home-based patient-centered healthcare delivery based on telenursing—the IMPACT study protocol - Roberto Cilia; Fabiana Colucci; Antonio Suppa; Francesca Valentino; Carmen Terranova; Catia Leuzzi; Jessica Cordasco; Giulia Fusi; Simona Floridia; Francesca De Giorgi; Roberta Telese; Arianna Braccia; et al. (Therapeutic Advances in Neurological Disorders)
Background: People with atypical parkinsonism, such as multiple system atrophy and progressive supranuclear palsy, experience a wide range of motor and non-motor symptoms associated with the increasing complexity of care delivery and the increased risk of complications and hospital admissions. Objectives: To investigate the efficacy and cost-effectiveness of a 12-month remote home-based integrated program aiming to improve healthcare delivery coordinated by a nurse specialized in the management of individuals with atypical parkinsonism (parkinsonism nurse specialist, PKNS) compared to the standard-of-care model. Design: Multicenter, randomized, single-blind, controlled clinical trial involving 164 individuals with atypical parkinsonism. Methods and analysis: Participants will be randomized 1:1 in intervention (PKNS) and control (standard-of-care) arms. Assessments will be undertaken at baseline and after 6 and 12 months. Primary outcome measure is the Parkinson’s Disease Questionnaire 39-items scale total score. Secondary measures include the clinical scales testing motor and non-motor symptoms, caregiver burden, adherence to therapy, cumulative disease burden and the number of unplanned hospital visits/admissions during the study period. The cost-effectiveness of this method will be evaluated by using the EuroQoL-5, which estimates the incremental cost per quality-adjusted life-years gain. Real-life motor autonomy will be objectively measured by collecting waist-worn wearable data on gait parameters (automatically detecting motor patterns indicative of freezing of gait and falls) in all subjects for five consecutive days each month during the 12-month duration of the study. Ethic: Study protocol has been approved by the ethics committee of all participating centers. The study is conducted according to good clinical practice and the Declaration of Helsinki. Discussion: An integrated remote care model at home coordinated by a specialized nurse in the management of parkinsonism (Telenursing) could offer significant benefits to patients and healthcare professionals through better health education, continuity of care, and careful monitoring of complications. Trial registration: ClinicalTrials.gov identifier NCT05792332.